Implementasi Nilai-Nilai Pancasila Dalam Pendidikan Sosial Sebagai Strategi Membangun Karakter Bangsa - Reyzaldi, Reyzaldi; Sujana, I Putu Windu Mertha; Landrawan, I Wayan; Pertiwi, Ni Ketut Santya Isana; Wahyudi, Putu Putri Audi Vebi; Muliani, Ketut Sri; Ramadhani, Muhammad Raditiya; Hidayati, Tri Nuri (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study generally examines Pancasila as the foundation of the state and ideology of the Indonesian nation, which contains fundamental values that serve as guidelines in the life of the nation and state. Amidst the challenges of globalization, technological advances, and rapid socio-cultural changes, strengthening national character through education has become very important. This study aims to analyze the implementation of Pancasila values in social education as a strategy for building a national character that is integrity, moral, and patriotic. The method used is library research by examining various scientific literature related to social education and Pancasila values. The results of the study show that social education plays a strategic role in instilling the values of Belief in God, Humanity, Unity, Democracy, and Justice through three main approaches, namely education about Pancasila, education through Pancasila, and education for Pancasila. These approaches have proven effective in strengthening national identity, student morality, and the spirit of democracy and social responsibility. However, their implementation still faces challenges such as low teacher competence, a technocratic curriculum, and the influence of global culture that is not in line with national values. The conclusion of this study confirms that Pancasila-based social education is key to shaping Indonesians with character and a national perspective. This implies that there needs to be synergy between schools, families, and communities to create an educational environment that is conducive to the comprehensive and sustainable internalization of Pancasila values.  Keywords: Pancasila, Social Education, and National Character